Separation of powers and political budget cycles - Alejandro Saporiti; Jorge M. Streb (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2003)
From a theoretical viewpoint, political budget cycles (PBC) arise in equilibrium when rational voters are imperfectly informed about the incumbent's competency and the incumbent enjoys discretionary power over the budget. This paper focuses on the second condition, examining how executive discretion is affected by the budgetary process under separation of powers. We specifically model PBC in the composition of government spending. The main result is that effective checks and balances in the budgetary process curb PBC. The institutional features of the executive-legislature bargaining game, namely, the actual agenda-setting authority, the status quo location and the degree of legislative oversight and control of the implementation of the budgetary law, play critical roles for the existence and the size of PBC. These results are consistent with recent empirical findings, which show that PBC are more pronounced in developing countries, where there are also less effective checks and balances.
Keywords: D72; D78; 330; rational political budget cycles; budget composition; separation of powers; checks and balances; budgetary process; Politischer Konjunkturzyklus; Öffentlicher Haushalt; Theorie